Vertical program of screenings and check-ups in the Russian Federation: design, implementation and lessons learnt - Igor Sheiman; Sergey Shishkin; Svetlana Sazhina (BMC, 2022)
Abstract Background The Russian Federation has introduced a vertical large-scale program of 'dispensarization' (Program) that includes health check-ups and screenings for the entire adult population. It is expected to improve the results of medical interventions and ensure health gains at a relatively low cost. The major research question: Does the design and implementation of the program meet the expectations? Methods We analyze regulatory acts and the literature on the design and the outcomes of the Program. Physicians' surveys and interviews are conducted to understand the capacity of primary care providers to meet the requirements of the Program, as well as the link between the early identification of new illnesses and their follow-up management, administration of the program, the barriers to its successful implementation. Results There is a substantial progress in the coverage of the population and increase in the number of identified illnesses. Some specific instruments of the Program implementation work well, others require more careful design and additional integrative and managerial activities. The capacity of primary care providers does not allow to provide high quality preventive services, as well as to ensure a continuum of preventive and curative work. The pattern of the Program administration facilitates its nation-wide implementation according to the unified rules, but makes it more difficult to account for the local conditions and limits the autonomy of professionals to choose specific population risk groups and a list of services. The interaction of providers in preventive activities is inadequate. Conclusion The expectations of the Program are too high due to the inconsistencies in its design and implementation. The major lesson learnt is that the program like this should meet the capacity of primary care and be designed as a complex of interrelated activities to identify illnesses and provide their follow-up management.